1995
DOI: 10.1139/f95-768
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen consumption, nitrogenous excretion, and filtration rates of Dreissena polymorpha at acclimation temperatures between 20 and 32 °C

Abstract: Mussels were acclimated to each of four experimental temperatures (20, 24, 28, and 32 °C) for 30 days. Mussels averaged 10.29 mg tissue dry weight. Oxygen consumption rates at 32 °C were 3.65 times larger than consumption rates at 20 °C (p < 0.01). Ammonia excretion rates at 32 °C were 4.9 times greater than those at 20 °C (p < 0.01). O:N ratios were >60 at 20 and 24 °C but declined (p < 0.01) at 28 and 32 °C to <40. Filtration rates, an estimate of feeding rates, were not significantly differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 16 publications
12
71
1
Order By: Relevance
“…Fanslow et al (1995), studying the same species in the Saginaw Bay (Great Lakes region), concluded that the maximum filtration levels were probably associated with the temperature, although indirectly, through a decrease in seston and consequent increase in the filtration rates. On the other hand, Aldridge et al (1995) did detect a negative relationship between the temperature and filtration rates in D. polymorpha, with filtration rates at 20-24ºC being significantly higher than at 28-30ºC. This result could be accounted for by the fact that the highest water temperatures in that region during summer did not exceed 24.5ºC.…”
Section: The Relationship Between Filtration Rates and Temperaturementioning
confidence: 77%
See 1 more Smart Citation
“…Fanslow et al (1995), studying the same species in the Saginaw Bay (Great Lakes region), concluded that the maximum filtration levels were probably associated with the temperature, although indirectly, through a decrease in seston and consequent increase in the filtration rates. On the other hand, Aldridge et al (1995) did detect a negative relationship between the temperature and filtration rates in D. polymorpha, with filtration rates at 20-24ºC being significantly higher than at 28-30ºC. This result could be accounted for by the fact that the highest water temperatures in that region during summer did not exceed 24.5ºC.…”
Section: The Relationship Between Filtration Rates and Temperaturementioning
confidence: 77%
“…The experimental design followed the same model as the experiments conducted with the Algamac-2000 ®. Aliquots were taken after 1, 2, and 3 h after the first contact with the animals, also being analyzed using a digital spectrophotometer at 720 nm, the most appropriate wavelength to detect the green algae (Aldridge et al,1995). Transmittance values of the solution containing the food were transformed into concentration (number of cells/ml) using standard curves.…”
Section: Experiments Using Scenedesmus Sp (Chlorophyceae -Chlorococcmentioning
confidence: 99%
“…By tracing the values of biological processes across a range of temperatures, it is possible to characterize, by simple parameters like the activation energy E a or the Q 10 value, the physiological patterns that will emerge as a consequence of expected temperature changes (Aldridge et al, 1995;Caron et al, 1986). In the case of biological processes crucial for the metabolic balance of plankton systems (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Water temperature is known to influence the life of aquatic organisms. Increasing temperature positively influences the growth and survival of aquatic organisms (Aldridge et al 1995).…”
Section: Water Quality Analysismentioning
confidence: 99%